Transforming growth factor‐β signaling is upregulated in sporadic inclusion body myositis. Issue 5 (1st February 2017) - Noda, Seiya; Koike, Haruki; Maeshima, Shinya; Nakanishi, Hirotaka; Iijima, Masahiro; Matsuo, Koji; Kimura, Seigo; Katsuno, Masahisa; Sobue, Gen
ABSTRACT: Introduction: In this study we aimed to determine whether transforming growth factor‐β (TGF‐β) signaling is dysregulated in sporadic inclusion body myositis (sIBM) muscle samples. Methods: We examined TGF‐β signaling markers in muscle samples from 24 sIBM patients and compared them with those from 10 dermatomyositis (DM) patients using immunohistochemistry and Western blot analyses. Results: Compared with the DM muscle fibers, the sIBM muscle fibers exhibited greater TGF‐β, TGF‐β receptor type I (TβRI), and TGF‐β receptor type II (TβRII) immunoreactivity in the cytoplasm, as well as greater phosphorylated Smad2 (pSmad2) immunoreactivity in the myonuclei. The signal intensities of TGF‐β, TβRI, and TβRII immunoreactivity correlated significantly with muscle fiber cross‐sectional areas. Western blot analyses indicated higher expression levels of TGF‐β, TβRI, TβRII, and pSmad2 in the sIBM muscle samples than in the DM muscle samples. Conclusions: These data indicate that upregulation of TGF‐β signaling may be an important molecular event in sIBM. Muscle Nerve 55: 741–747, 2017